Maluku folktales: Character education values, opportunities, and challenges in Indonesian language learning - Aria Bayu Setiaji; Nanik Handayani; Tuti Alwiyah; Ilham Syahputra Hitjah (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2026)
As a cultural product, Maluku folktales emerge from traditions, origins, and customary rituals that contain moral messages, harmony, tolerance, and life wisdom. In the context of education, it is important to teach folktales as a means of cultural preservation and character building. The purpose of this study is to describe the value of maluku folklore, opportunities, and challenges in Indonesian Language learning. This study uses a qualitative descriptive-analytical approach. The primary data consist of interviews with teachers, students, and literature experts, while the secondary data include documents and folktale publications from The Maluku Language Office and the Department of Education and Culture. The findings reveal that Maluku folktales have significant potential as Indonesian language teaching materials that incorporate character education. From the twenty folktales analyzed, legends dominate because they contain concrete moral values and simple narrative structures that are easily understood by students. Their intrinsic elements present themes, protagonists embodying leadership and courage, and natural settings that foster ecological awareness. The moral messages emphasize honesty, togetherness, hard work, patriotism, and environmental care, which are aligned with the Pancasila Student Profile. Maluku folktales are therefore relevant for strengthening literacy, character education, and cultural preservation. Nevertheless, their utilization still faces challenges, particularly the limited availability of teaching resources and the lack of technology-based innovation. Therefore, integrating folktales into Indonesian language learning through digital media, P5 projects, and teacher training becomes a strategic step to support the Merdeka Curriculum while strengthening the cultural identity of the younger generation.